Relationship between self-efficacy and interdialytic weight gain (IDWG) index in people with chronic renal failure - Pratama, Eka Firmansyah (Indonesian Nursing Journal, 2024)
Background: Weight gain due to excess fluid in patients undergoing hemodialysis leads to shortness of breath and heart failure. Self-efficacy plays an important role in a person's ability to organize and carry out the programs of action needed to cope with situations that arise. Purpose: To analyze the correlation between self-efficacy and IDWG index in patients with chronic kidney disease. Methods: This study was conducted on chronic kidney disease patients in the hemodialysis room of RSUD Otanaha using a correlational research design with a cross-sectional approach. A total of 60 respondents were recruited using the purposive sampling technique. Data collection was done using a self-efficacy questionnaire and an IDWG observation sheet. Data analysis using the Pearson correlation test. Results: The results of this study showed a mean self-efficacy of 23.4 and a mean IDWG of 2.7. The results of the Pearson correlation test analysis yielded a p-value of 0.03 (<0.05), indicating that self-efficacy is related to IDWG scores in patients with chronic kidney disease. Conclusion: It can be concluded that good self-efficacy can reduce the IDWG index, and it is recommended that this research be used as reference material and provide nursing interventions in the form of education on the application of self-efficacy.